USE OF INTERFERON BETA-1A FOR INTRAMUSCULAR ADMINISTRATION IN CHILDREN AND ADOLESCENTS WITH MULTIPLE SCLEROSIS: EFFICACY, SAFETY AND ADHERENCE TO THERAPY - O.V. Bykova; T.V. Sidorenko; A.N. Platonova; N.V. Gol'tsova; L.M. Kuzenkova; A.N. Boiko (Union of pediatricians of Russia, 2009)
Immunomodulatory drugs reduce relapse rate and disease progression in relapsing-remitting multiple sclerosis but extensive data are not available on the effectiveness and tolerability of these drugs in childhood or adolescence. Interferon beta tolerability biased by frequency and method of drug administration. Drug administration has great impact on treatment compliance and adherence. That's why we discuss moreover interferon beta 1a intramuscular as perspective immunomodulative medication in pediatric MS cohort.Key words: immunomodulatory drugs, interferon beta, multiple sclerosis, compliance, adherence, adolescence, childhood.